Penguatan Kapasitas Ibu-Ibu PKK Kemiling Permai Dalam Menjaga Kesehatan Pencernaan Dengan Kombucha - Elma Viorentina Sembiring; Isnenia; Yulyuswarni (STIKES Columbia Asia Medan, 2026)
Digestive health in children plays a vital role in their overall growth and development. Diarrhea remains the most frequent illness occurring among children. The use of probiotics can both treat and prevent this condition. Kombucha is a fermented beverage that can function as a probiotic source. The objective of this activity was to educate members of the PKK (Family Welfare Movement) regarding probiotics and to practice making probiotics at home. The methodology employed a combination of counseling, demonstrations, and hands-on practice. The results of this activity showed an increase in knowledge among all participants concerning probiotics. Participants were enthusiastic and eager during the direct practice of brewing kombucha. Overall, this activity provided a positive impact on the PKK members, with the hope that it can be maintained sustainably to establish the home as the primary foundation for health.